Effect of the Sarcolemmal KATP Channel Blocker HMR1098 on Arrhythmias Induced by Programmed Electrical Stimulation in Canine Old Myocardial Infarction Model: Comparison With Glibenclamide - Bing-Mei Zhu; Shigeki Miyamoto; Yoshinobu Nagasawa; Teruaki Wajima; Keitaro Hashimoto (Elsevier, 2003)
ABSTRACT: The blockade of myocardial KATP channels may be antiarrhythmic for ischemic arrhythmias. A new sulfonylthiourea, HMR1098 (1-{5-[2-(5-chloro-o-anisamido)ethyl]-2-methoxyphenylsulfonyl}-3-methylthiourea, sodium salt), was demonstrated to be a cardioselective KATP-channel antagonist and to suppress arrhythmias during acute ischemia. We investigated effects of HMR1098 on the arrhythmias induced by programmed electrical stimulation (PES) in a canine old myocardial infarction model. HMR1098 (3 mg/kg, i.v.) significantly improved the scores of PES-induced ventricular arrhythmias, without changing the blood glucose concentrations. A classical sulfonylurea, glibenclamide (1 mg/kg, i.v.), had no significant effects on these arrhythmias, but reduced the blood glucose and increased the plasma insulin concentrations.